(untitled) (EduMa: Mathematics education learning and teaching, 2012)
Creativity-based independent study students is done through the computer to encourage students to do the analysis and improvement of knowledge, explore, exploit and manage information, and generate information and knowledge itself. Students can make the exploration of knowledge independently. Learning materials developed through the model vary from the very day CBL introduction of the computer, interacting with the computer, the use of specific software (word processors, spreadsheets, or databases) and the creation of learning programs through a programming language. Conventional education system is in progress at this time start to have problems in relation to the needs of 21st century education. Learning still tend in the direction of the pattern, where more dominate role of the learning process. Students tend to be regarded as an object with the same potential so that plurality is not a part of the students in the learning process. The objective of the research development of this learning module is a learning algorithm based multimedia and programming that helps the learning process in the academic environment, enabling students to accelerate the understanding of the teaching materials, especially algorithms and programming and to give freedom to students to make learning an explorative and repetitive at - discussion of each subject so that teaching materials for possible use by students with learning the various characters. Model development system using the method of prototyping are approaches to software development approach using a model of instructional design / development with the approach followed by the model system. model generally recommend this approach, the sequence of activity that includes analysis, design, development, implementation, and evaluation (ADDIE) Keywords: Computer based learning (CBL), learning, algorithms and programming, multimedia